Plant growth-promoting root-colonizing bacterial endophytes - Adeleke, Bartholomew Saanu; Babalola, Olubukola Oluranti; Glick, Bernard R. (Rhizosphere, 2021)
The development of an environmentally friendly agricultural system as opposed to conventional methods using chemical fertilizers and pesticides for improved crop productivity is a promising aspect of modern agricultural biotechnology. Current research has focused on using free-living microbes that can colonize the plant endosphere as a means of enhancing crop productivity. In the plant rhizosphere, the complex root matrix facilitates microbe-microbe, microbe-plant, and soil-microbe interactions in establishing microbial communities, which precede endophytic colonization of the plant by some of these microbes. Endophytic microbes play an important role in plant growth promotion, as they employ direct or indirect mechanisms to facilitate plant growth by producing phytohormones and various secondary metabolites. The roles of endophytic microbes in sustaining plant growth under biotic and abiotic stresses through these mechanisms can provide insights into their envisaged putative functions in establishing host plant interactions for maximum use in the agricultural sector as an ecofriendly alternative tool to improve crop yield. In addition, a better understanding of endophytic bacteria functions in agriculture, medicine, biotechnology, and industry may enable scientists to unlock several opportunities by exploring valuable endophytic bioproducts in the recent application as bioinoculants, biostimulants, and environmental safety in pollution control and phytoremediation. Furthermore, the genomic insights into endosphere biology can provide detail structural diversity and functional profiling of endophytic microbiome for possible recommendations in future agriculture as a source of the organic amendment. Hence, this review emphasis on the root-colonizing endophytic bacteria and their importance in modern agricultural biotechnology. •Plant-microbes interaction and importance in agriculture.•Endophytes and importance in crop imrovement•Microbial gene competent and survival in environment.•Chemical fertilizer versus organic fertilizer, best choice in sustainable agriculture.•Identifiable endophytes as an asset in agriculture, pharmaceutical and industry.